High infection level of a snake, Xenodon merremii (Wagler in Spix, 1824) (Serpentes: Dipsadidae), with Serpentirhabdias cf. vellardi (Pereira, 1928) (Nematoda: Rhabdiasidae) in Brazil - Emmerich, Enzo [UNESP]; Morais, Drausio Honorio; Da Silva, Reinaldo José [UNESP] (Helminthological Society, 2018)
One Xenodon merremii specimen was reported with a high number of a rhabdiasid nematodes in the lungs. The snake died shortly after its arrival in our laboratory after capture in the municipality of Saõ Manuel, Saõ Paulo State, Brazil. Necropsy revealed the presence of 13,526 nematodes, which we identified as Serpentirhabdias cf. vellardi, infecting the snake's lungs. A detailed morphological characterization of this nematode species and a discussion of the known cases of infection with Serpentirhabdias spp. are presented.
Keywords: disease; hyperinfection; lung; nematode; parasite morphology